Jaringan Ulama: Penyebaran dan Pembaharuan Pendidikan Islam di Nusantara - Setiawan, Agus Mahfudin; Hasanah, Uswatun; Nabilla, Nabilla (Islamic Education, 2022)
In this article, the author re-explores the dynamics of the educational journey in the archipelago with various policies of the Dutch colonial period to the arrival of Islam which has transformed. The role of Nusantara scholars brought about a change in the face of education in the archipelago which was previously organized by the Dutch colonial government with a system that was discriminatory and religiously neutral. The network of clerics began by establishing trade relations between Muslims of the Archipelago in the coastal region. After gaining political power, it then penetrated the bureaucracy, namely the Islamic Sultanate. At this, stage Islam comes by emphasizing the introduction of Islamic values in society. Furthermore, the education system developed with the existence of Surau or Langgar (small mosque) and developed into an Islamic boarding school. Educational renewal materials unite Islamic values, with the content of science and technology.